Novel behavioural and molecular determinants and indicators of attention deficit-/hyperactivity disorder in adults. - Alison Louise Baird (2011)
Attention deficit-/hyperactivity disorder (ADHD) is a psychiatric condition that can affect both children and adults. It is characterised by behavioural and attention difficulties. Sleep deficits are a prominent characteristic of the disorder and some of the core symptoms of ADHD are known characteristics of sleep deprivation. The circadian clock is integral to determining the rhythm of the sleep/wake cycle. Furthermore the two main forms of pharmacological treatment for ADHD, namely the psychostimulant methylphenidate, and the non-stimulant atomoxetine, along with the targets of these drugs noradrenaline and dopamine, appear to both interact and be under the regulation of the circadian clock.This thesis aimed firstly to develop a non-invasive technique for the real time RT- PCR quantification of circadian clock gene expression in the human oral mucosa. Secondly to address how circadian clock functioning may be disturbed in adult ADHD via measurement of a number of molecular, endocrine and behavioural markers, for which real-time RT-PCR, ELISA and actigraphy techniques were employed. Thirdly to examine the effects of ADHD medication upon circadian clock protein expression in the rodent brain using immunohistochemistry methods.Here it is demonstrated that disturbances in the rhythmic secretion of endocrine factors that are key outputs and regulators of the master circadian pacemaker, the circadian clock gene expression of a peripheral oscillator and the actigraphic measures of circadian organization of gross behaviour are associated with adult ADHD. Furthermore, both atomoxetine and methylphenidate are shown to effect circadian clock protein expression. Collectively this data suggests a key role for the circadian clock not only in the pathophysiology of adult ADHD but also indicates a role for pharmacological treatments in the modulation of the circadian clock.